Field‐Induced n‐Doping of Black Phosphorus for CMOS Compatible 2D Logic Electronics with High Electron Mobility. (11th August 2017) - Xu, Yijun; Yuan, Jian; Zhang, Kai; Hou, Yuan; Sun, Qiu; Yao, Yingming; Li, Shaojuan; Bao, Qiaoliang; Zhang, Han; Zhang, Yuegang
Abstract : Black phosphorus (BP) has been considered as a promising two‐dimensional (2D) semiconductor beyond graphene owning to its tunable direct bandgap and high carrier mobility. However, the hole‐transport‐dominated characteristic limits the application of BP in versatile electronics. Here, we report a stable and complementary metal oxide semiconductor (COMS) compatible electron doping method for BP, which is realized with the strong field‐induced effect from the K + center of the silicon nitride (Six Ny ). An obvious change from pristine p‐type BP to n type is observed after the deposit of the Si x N y on the BP surface. This electron doping can be kept stable for over 1 month and capable of improving the electron mobility of BP towards as high as ~176 cm 2 V –1 s –1 . Moreover, high‐performance in‐plane BP p‐n diode and further logic inverter were realized by utilizing the n‐doping approach. The BP p‐n diode exhibits a high rectifying ratio of ~10 4 . And, a successful transfer of the output voltage from "High" to "Low" with very few voltage loss at various working frequencies were also demonstrated with the constructed BP inverter. Our findings paves the way for the success of COMS compatible technique for BP‐based nanoelectronics. Abstract : A stable and complementary metal oxide semiconductor (CMOS) compatible electron doping strategy for black phosphorus is realized with a field‐induced effect. The effective electron doping with highly improved electron mobility enables the fabrication of high‐performance logic devices, including a PN diode with rectifying ratio up to ≈10 4 and an inverter that is compatible with various driving frequencies.